2012
DOI: 10.1111/1462-2920.12011
|View full text |Cite
|
Sign up to set email alerts
|

Dryland biological soil crust cyanobacteria show unexpected decreases in abundance under long‐term elevated CO2

Abstract: Biological soil crusts (biocrusts) cover soil surfaces in many drylands globally. The impacts of 10 years of elevated atmospheric CO2 on the cyanobacteria in biocrusts of an arid shrubland were examined at a large manipulated experiment in Nevada, USA. Cyanobacteria-specific quantitative PCR surveys of cyanobacteria small-subunit (SSU) rRNA genes suggested a reduction in biocrust cyanobacterial biomass in the elevated CO2 treatment relative to the ambient controls. Additionally, SSU rRNA gene libraries and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 76 publications
1
40
0
1
Order By: Relevance
“…Cyanobacteria qPCR measured the abundance of Cyanobacteria 16S rRNA genes, acting as a secondary measure of cyanobacterial biomass. The Cyanobacteria qPCR was performed with primers that target the V2 to V4 variable regions, using CYA 359 (5=-GGGGAATYTTCCGCAATGGG-3=) and an equimolar mixture of CYA-781RA (5=-GACTACTGGGGTATCT AATCCCATT-3=) and CYA-781RB (5=-GACTACAGGGGTATCTAATC CCTTT-3=) with reaction mixtures, standards, and thermocycling conditions as previously described (27,28). Analysis of variance (ANOVA) was used for treatment comparisons of the DNA, chlorophyll a, and qPCR data sets, followed by pairwise t tests (Arches or ISKY, where two treatments were performed) or Tukey's honestly significant difference (HSD) mean separation procedure (CV experiment, where four treatments were performed) using the JMP software package.…”
Section: Methodsmentioning
confidence: 99%
“…Cyanobacteria qPCR measured the abundance of Cyanobacteria 16S rRNA genes, acting as a secondary measure of cyanobacterial biomass. The Cyanobacteria qPCR was performed with primers that target the V2 to V4 variable regions, using CYA 359 (5=-GGGGAATYTTCCGCAATGGG-3=) and an equimolar mixture of CYA-781RA (5=-GACTACTGGGGTATCT AATCCCATT-3=) and CYA-781RB (5=-GACTACAGGGGTATCTAATC CCTTT-3=) with reaction mixtures, standards, and thermocycling conditions as previously described (27,28). Analysis of variance (ANOVA) was used for treatment comparisons of the DNA, chlorophyll a, and qPCR data sets, followed by pairwise t tests (Arches or ISKY, where two treatments were performed) or Tukey's honestly significant difference (HSD) mean separation procedure (CV experiment, where four treatments were performed) using the JMP software package.…”
Section: Methodsmentioning
confidence: 99%
“…At the same Desert FACE site, molecular and metagenomic analyses of the biocrust bacterial community showed that cyanobacteria exhibited reduced total biomass and constituted a lower proportion of the biocrust bacterial community after 10 years of elevated CO 2 relative to the ambient CO 2 controls (Haimovich-Dayan et al 2011;Steven et al 2012). Functional analyses of biocrust metagenomes showed that cyanobacterial genes related to oxidative stress responses were higher in biocrusts exposed to elevated CO 2 conditions compared to ambient conditions, suggesting that increased oxidative stress may play a role in the cyanobacterial response (Steven et al 2012). Thus, the photosynthetic cyanobacteria in biocrusts responded negatively to long-term elevated CO 2 conditions in the field, highlighting the complexity of biocrust community responses to changing CO 2 concentrations.…”
mentioning
confidence: 99%
“…Growth and N 2 fixation in N 2 -fixing plants can respond positively to elevated CO 2 (Cernusak et al, 2011), but in many cases these responses are absent, e.g., N-fixers in temperate grasslands (Garten et al, 2008;Zhang et al, 2011), Alnus (Temperton et al, 2003;Millett et al, 2012), and ocean cyanobacteria (Czerny et al, 2009;Law et al, 2012). Chronic CO 2 exposure was found to reduce cyanobacterial abundance in desert crusts (Steven, 2012). Our finding that nonsymbiotic 3332 B.…”
Section: Effects Of Co 2 On N 2 Fixationmentioning
confidence: 59%